Theatre training and performance practice in neoliberal Zimbabwean universities: survival strategies and frustrations. Issue 3 (3rd July 2019) - Sibanda, Nkululeko
ABSTRACT: In this paper, I document and discuss the frustrations and survival strategies of Theatre Arts and/ or Performing Arts departments in STEMatised neoliberal Zimbabwean universities. I submit that while these departments devised creative survival strategies which kept them relevant and competitive for some time, they also relegated them to the academic periphery, with no student uptake. Through case studying the University of Zimbabwe's Theatre Arts Department and Great Zimbabwe University's Performing Arts Department, I argue that this neoliberal transformation of Zimbabwean universities put pressure on theatre training, performance practice, and practitioners to adapt to 'scientific' methodologies so as to access funding and recognition.